EFFECT OF CYNICISM TOWARDS ENVIRONMENTALLY RESPONSIBLE PURCHASE BEHAVIOUR OF ENERGY EFFICIENT VEHICLE AMONG MALAYSIAN CONSUMERS - SHUKOR, Muhamad Syakir; SULAIMAN, Zuraidah; AI CHIN, Thoo; MAS’OD, Adaviah (Studia Universitatis Babeș-Bolyai Negotia, 2019)
Objective: One of the toughest challenges in social marketing is behaviour intervention. Previous researchers have developed various models and theories to simultaneously examine behaviour changes and their effects. Due to resources scarcity and global warming, automakers have come out with an innovative idea of Energy Efficient Vehicle (EEV) which has been a great improvement in the automotive industry. This invention targets for behavioural change or behavioural adoption for consumers to adjust their preferences from a conventional vehicle to EEV. High market growth in the automotive industry has encouraged social marketers, policymakers, governments, and academics to propose suitable intervention approach in motivating preferences toward EEV. Using the context of the purchase intention of EEV in Malaysia, this conceptual research paper applies Environmental Responsible Behaviour (ERB) model to evaluate the causal model of materialism, environmental belief and environmental concern transcend on Purchase Intention of EEV. Methodology: This study proposed an explanatory quantitative method. Using a partial least squares approach, the measurement model for this study is presented. Implication: This research presents a conceptually supported framework to describe the moderating role of cynicism on the relationship between environmental concern with purchase intention of EEV due to rising issues of greenwashing in the automotive industry. The study is particularly useful by providing insights in assisting the stakeholders and automotive industry players on promoting the pro-behaviour toward EEV. This paper also provide additional review of Environmental Responsible Behaviour (ERB) model that been derived from Values, Belief and Norms theory (Stern et al., 1995). JEL CLASSIFICATION: M31